Star Metro, 05 Julai 2007 - Dharmender Singh (Star Publications (Malaysia) Berhad, 2007)
The Selangor Religious Department (JAIS)is keeping a close eye on those involved with Rufaqa' Corporation Sdn Bhd after receiving information that its members were planning a name change again to fool the authorities